The Role of Tapak Suci Pencak Silat Martial Arts Teacher in The Development of Youth in Medan City - Redha Azmi Kamal; Robert Sibarani; Agus Purwoko (East Asian Journal of Multidisciplinary Research, 2023)
Organization college art self-defence halibut silat is organization society, which teaches knowledge martial arts also teaches method For do coaching to its members. Giving guidance by the organization college art self-defence pencak silat footprint holy aim for formation favor noble character. Formulation the problem How role organization college art self-defence pencak silat in follow do development of youth, its role and strategy. Method research used use juridical normative through approach qualitative, with relying on primary and secondary data, location research in organizations college art self-defence pencak martial arts located in the city of Medan from results study analyzed and compiled in a manner systematic.